Abiotic drivers of co‐occurrence and diversity patterns of Calopterygidae species in Amazonian protected freshwaters - Brito, Joás Silva; Silva, Everton Cruz; Cruz, Gabriel Martins; Ferreira, Victor Rennan Santos; Bastos, Rafael Costa; Monteles, Josinete Sampaio; Mendoza‐Penagos, Cristian Camilo; Carvalho, Fernando Geraldo; Oliveira‐Junior, José Max Barbosa; Dias‐Silva, Karina; Michelan, Thaisa Sala; de Assis Montag, Luciano Fogaça; et al. (Wiley, 2025)
Abstract Interspecific competition, environmental conditions and spatial factors can shape species co‐occurrence patterns in freshwater habitats, especially among closely related taxa. We investigated the diversity and co‐occurrence patterns of damselflies from the Calopterygidae family in streams located inside protected areas (IPAs) and outside protected areas (OPAs) in the Brazilian Amazon, assessing the influence of abiotic variables. We expected that IPA streams would show greater environmental heterogeneity, stronger co‐occurrences and fewer random associations than OPA streams. We also predicted that environmental variables would have a stronger influence on species diversity and co‐occurrence patterns than spatial predictors. A total of 359 individuals representing 10 Calopterygidae species were collected from 98 streams across 4 PAs. Contrary to our expectations, OPA streams showed higher environmental heterogeneity, potentially related to human disturbances. Negative co‐occurrence prevailed in both IPA and OPA streams, but was more pronounced in IPA sites. These patterns may reflect ecological similarity among Calopterygidae species, particularly in resource use. Canonical analyses revealed a stronger influence of broad‐scale spatial variables on diversity and co‐occurrence than initially predicted, with two major Amazonian rivers likely acting as dispersal barriers. Limnological and physical habitat variables were also significant predictors, likely related to the availability of exploitable resources. Future research should extend this approach to other damselfly families and aquatic groups and examine the role of morphological traits in mediating species interactions.